What do troubled adolescents expect from their GPs?. (1st October 2016) - Tudrej, Benoit V.; Heintz, Anne-Laure; Ingrand, Pierre; Gicquel, Ludovic; Binder, Philippe
Abstract: Background: Adolescents often have emotional and behavioural problems that general practitioners are likely to miss. While nearly 80% of them consult their GP every year, it is usually for physical, not psychological reasons. Trust in their GPs in necessary for screening. Objectives: To identify the key quality desired by adolescents for them to feel free to confide in GPs. To determine whether this quality differed according to gender, level of at-risk behaviours or interlocutor: friend, parent or GP. Methods: A descriptive cross-sectional study was conducted in 182 French educational institutions chosen by lot. Fifteen-year-olds completed a self-administered questionnaire under examination conditions. While the questions on behaviour were drawn from the cross-national survey entitled 'Health behaviour in school-aged children (HBSC), ' the questions on conditions conducive to trust were drawn from previous studies. Results: A total of 1817 (911 boys, 906 girls) questionnaires were analysed. Adolescents said they seldom confided. The main quality they expected from a GP to whom they could confide in was 'honesty', which meant ensuring secrecy, refraining from judgment, and putting forward the right questions. This priority was modified by neither gender nor experience with health-risk behaviour. The quality of 'reliability' was more closely associated with their parents or friends, while 'emotionality' was cited less often. Conclusion: To gain the trust of adolescents, GPs have to be sincere and non-manipulative and have the ability to ensure confidentiality and to put forward the right questions without passing judgment. Can this be verified during consultations? Prospective studies could shed light on this point.